Method for implanting organic functional group ions into magnesium alloy

By coating the PLGA coating on the surface of the magnesium alloy and introducing imidazole ions, the problems of excessive corrosion rate and insufficient biocompatibility of the magnesium alloy are solved, and the corrosion resistance and biocompatibility of the magnesium alloy are significantly improved.

CN119530743APending Publication Date: 2025-02-28TAIYUAN INST OF TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411722610.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Magnesium alloys corrode too fast in the physiological environment, resulting in failure of mechanical support and problems with biocompatibility, such as the toxicity of aluminum and rare earth elements.

Method used

The method of organic functional group ion implantation of magnesium alloy is used to improve the corrosion resistance and biocompatibility of magnesium alloy by coating PLGA coating on the surface of magnesium alloy and introducing imidazole ions using ion implantation technology.

Benefits of technology

It effectively improves the corrosion resistance and biocompatibility of magnesium alloys, extends its application life in the field of biomedical science, and reduces the risk of toxicity to the human body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530743A_ABST
    Figure CN119530743A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ion implantation, and discloses a method for implanting organic functional group ions into magnesium alloy, which comprises the following steps: preparing a magnesium alloy sample; surface pretreatment: coating a PLGA solution on the sample, and naturally drying to form a PLGA coating; fixing the sample on ion implantation equipment and then vacuumizing; precursor gas preparation: gasifying imidazole and conveying the gasified imidazole to an ion source area; ionizing the imidazole; the imidazole ions are accelerated to 80keV energy; ions are injected according to the injection dose of 1 * 1017 ions / cm < 2 > and the beam density of 1 [mu] A / cm < 2 >, and the injection depth is about 100 nm; and annealing treatment is conducted, and after annealing is finished, natural cooling is conducted to room temperature. The PLGA coating is coated on the surface of the magnesium alloy, so that the corrosion resistance and the biocompatibility of the magnesium alloy can be effectively improved, and the application range of the magnesium alloy in the field of biomedicine is expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ion implantation, and in particular to a method for implanting organic functional group ions into a magnesium alloy. Background Art

[0002] Biomaterials are commonly used bone substitutes in orthopedic surgery and are fixation and stabilization devices for fractures, ligament and tendon repair, and total hip replacement. Among them, magnesium alloys are well tolerated by the human body, have extremely low toxicity, are rapidly excreted, and show a variety of biologically active effects, including promoting bone regeneration and protecting against oxidative stress. Magnesium alloys can be safely degraded in the body without the need for secondary surgery to remove them. They avoid the problems of stress shielding, chronic inflammation, thrombosis, etc. that exist in permanent materials such as stainless steel, titanium alloys, and cobalt-chromium alloys.

[0003] Despite this, in a physiological environment, magnesium alloys still have the problem of excessively fast corrosion rates that cause mechanical support failure. Common magnesium alloys include Mg-Al (magnesium aluminum), Mg-RE (magnesium rare earth), Mg-Zn (magnesium zinc) based alloys, etc. Mg-Al based alloys are considered to be industrially available biomaterials due to their good mechanical properties and versatility. However, experimental studies have shown that aluminum has the problems of inducing neurotoxicity, causing Alzheimer's disease, damaging muscles, and reducing bone cell activity. Mg-RE alloys have good mechanical properties and corrosion resistance, but large doses of rare earth elements are highly toxic. Therefore, in order to ensure the biocompatibility of Mg-RE alloys, they can only be used in a quantitative manner. Mg-Zn alloys have high strength and ductility, but the cost is relatively high.

[0004] In summary, it is urgent to design and develop a magnesium-based biodegradable implant material with slow corrosion rate and low toxicity to the human body. Summary of the invention

[0005] In view of this, the present invention proposes a method for implanting organic functional group ions into magnesium alloys, aiming to solve the problem in the current technology that the corrosion rate of magnesium alloys is too fast, resulting in failure of mechanical support.

[0006] The present application proposes a method for implanting organic functional group ions into a magnesium alloy, comprising:

[0007] Sample preparation;

[0008] Surface pretreatment: coating the sample with PLGA solution and drying it naturally to form a PLGA coating;

[0009] The sample is fixed on the ion implantation device and then vacuumed;

[0010] Precursor gas preparation, vaporizing imidazole and delivering it to the ion source region; ionizing imidazole; accelerating imidazole ions to 80 keV energy; 17ions / cm 2 Implantation dose and 1μA / cm 2 Ions were implanted at a beam density of 100 nm and an implantation depth of 100 nm.

[0011] After annealing, the process is followed by natural cooling to room temperature.

[0012] Optionally, the surface pretreatment is performed by coating with a spin coater, and the coating parameters are a rotation speed of 3000 rpm and a time of 30 seconds.

[0013] Optionally, the vacuum degree of the vacuum pumping is ≤10 -6 Torr.

[0014] Optionally, the operation of gasifying imidazole in the preparation of the precursor gas is: heating the imidazole to 150° C. to gasify it.

[0015] Optionally, the ionized imidazole is specifically: in an ion source region, gaseous imidazole is ionized by electron bombardment to generate imidazole ions.

[0016] Optionally, during the preparation of the precursor gas, the sample temperature is maintained below 50° C. by a cooling system to prevent overheating damage.

[0017] Optionally, the specific steps of the annealing treatment are:

[0018] After the injected sample is placed in a temperature-controlled annealing furnace, the argon protection system is started, the argon flow rate is set to 100 mL / min, the annealing temperature is set to 200° C., and the time is set to 1 hour.

[0019] Optionally, the magnesium alloy sample preparation includes:

[0020] Mechanical polishing: Use 600, 800, 1200 and 1500 grit sandpaper to polish the magnesium alloy sample in sequence until the surface is smooth without obvious scratches;

[0021] Chemical cleaning: Use ethanol and deionized water to ultrasonically clean the samples for 10 minutes each time to remove surface oil and impurities; soak the samples in 5% nitric acid solution for 1 minute to remove the oxide layer, and then rinse with deionized water;

[0022] Drying: The cleaned samples were placed in an oven at 50°C for 30 minutes.

[0023] Compared with the prior art, the present invention has the following beneficial effects: since a layer of PLGA coating is applied on the surface of the magnesium alloy, the corrosion resistance and biocompatibility of the magnesium alloy can be effectively improved, thereby expanding its application range in the biomedical field. By using a spin coater for surface pretreatment, it can be ensured that the PLGA coating is evenly applied on the surface of the magnesium alloy, further improving the stability and reliability of the coating. During the ion implantation process, by controlling the vacuum degree at ≤10 -6 Torr, which can avoid the influence of impurity gases on the injection process and ensure the purity and effect of ion injection. Heating imidazole to 150°C for vaporization is beneficial to improve the gasification efficiency of imidazole, thereby ensuring the imidazole ion concentration in the ion source area and further improving the effect of ion injection. Using electron bombardment to ionize gaseous imidazole can effectively convert imidazole molecules into imidazole ions, which is beneficial to the subsequent ion injection process. When preparing the precursor gas, the cooling system is used to keep the sample temperature below 50°C to prevent the sample from being damaged by overheating, ensuring the safety and stability of the sample. During the annealing process, the structural stability and performance of the magnesium alloy sample after injection can be effectively improved by starting the argon protection system and controlling the annealing temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. Moreover, the same reference symbols are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:

[0025] Figure 1 Schematic diagram of the hardness and elastic modulus of the magnesium alloy after imidazole ion implantation provided in an embodiment of the present invention, wherein a is a hardness test diagram and b is an elastic modulus test diagram. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] The present application proposes a method for implanting organic functional group ions into a magnesium alloy, comprising:

[0028] Magnesium alloy sample preparation;

[0029] Surface pretreatment: Coating the sample with PLGA solution and letting it dry naturally to form a PLGA coating;

[0030] The sample is fixed on the ion implantation device and then vacuumed;

[0031] Precursor gas preparation: vaporize imidazole and deliver it to the ion source area; ionize imidazole; accelerate imidazole ions to 80 keV energy; 17 ions / cm 2 Implantation dose and 1μA / cm 2 Ions are injected at a beam density of about 100 nm.

[0032] After annealing, the process is followed by natural cooling to room temperature.

[0033] It is understood that the present application proposes a method for implanting organic functional group ions into magnesium alloys, which improves the performance of magnesium alloys, especially in terms of corrosion resistance and biocompatibility, through a series of steps. The following are the specific steps of the method: Preparation of magnesium alloy samples: First, it is necessary to prepare magnesium alloy samples, which may include selecting suitable magnesium alloy materials, preparing them into the required shape and size, etc. Surface pretreatment: Coat the surface of the magnesium alloy sample with polylactic acid-glycolic acid (PLGA) solution and dry it naturally to form a PLGA coating. PLGA is a biodegradable polymer with good biocompatibility and can be used as an implant material. Fixing the ion implantation equipment: Fix the pretreated magnesium alloy sample on the ion implantation equipment, and then perform vacuum treatment to create a vacuum environment, which is conducive to the subsequent ion implantation process. Preparation of precursor gas: Gasify imidazole and transport it to the ion source area. Imidazole is an organic compound that can be used as a precursor for ion implantation. Ionized imidazole: In the ion source area, imidazole is ionized to form an ion beam. Accelerated ion implantation: The ion beam is accelerated to an energy of 80 keV, and then 1×10 17 ions / cm 2 The implantation dose and 1μA / cm 2 The beam density is injected into the magnesium alloy sample. The implantation dose refers to the number of ions implanted, while the beam density refers to the current density of the implanted ion beam. Annealing: After the ion implantation is completed, the sample is annealed to improve the performance and uniformity of the implanted layer. Natural cooling: After the annealing treatment is completed, the sample is naturally cooled to room temperature.

[0034] Through this ion implantation method, organic functional groups can be introduced on the surface of magnesium alloys, thereby improving their corrosion resistance and biocompatibility, making them more suitable as biomedical implant materials. This method provides an effective way to improve the properties of magnesium alloys so that they can meet the needs of specific applications.

[0035] In this preferred embodiment, the surface pretreatment is performed by coating with a spin coater, and the coating parameters are a rotation speed of 3000 rpm and a time of 30 seconds.

[0036] In this preferred embodiment, the vacuum degree of the vacuum pumping is ≤10 -6 Torr.

[0037] It is understood that during the surface pretreatment process, a spin coater was used to apply the PLGA solution, which is a common laboratory technique for uniformly coating a liquid on a solid surface. In a preferred embodiment, the coating parameters of the spin coater are set to a rotation speed of 3000 rpm and a time of 30 seconds. The selection of these parameters helps to ensure that the PLGA solution can be uniformly coated on the surface of the magnesium alloy sample to form a uniform PLGA coating. In addition, the vacuum degree of the vacuum pump is set to ≤10 - 6 Torr, which is a very high vacuum degree, is usually used in high vacuum environments such as ion implantation in scientific research and industrial production. Under this vacuum degree, air molecules in the sample and the implantation equipment can be effectively removed, and the interaction between air molecules and the ion beam can be reduced, thereby improving the efficiency and quality of ion implantation. It can be seen that the selection of surface pretreatment and vacuum parameters in the preferred embodiment is to ensure the uniformity of the PLGA coating and the efficiency and quality of the ion implantation process, thereby improving the performance and uniformity of the final implantation layer.

[0038] In this preferred embodiment, the operation of gasifying imidazole in the preparation of the precursor gas is: heating the imidazole to 150° C. to gasify it.

[0039] In this preferred embodiment, the ionized imidazole is specifically: in the ion source region, the gaseous imidazole is ionized by electron bombardment to generate imidazole ions.

[0040] It is understood that during the preparation of the precursor gas, imidazole is heated to 150°C to convert it from a solid state to a gaseous state. This step is necessary because imidazole is solid at room temperature and needs to be heated to convert it to a gaseous state for the subsequent ionization process. In the specific operation of ionizing imidazole, electron bombardment is used. The electron bombardment method is a physical process in which a high-energy electron beam is applied in the ion source region, and the electrons interact with the gaseous imidazole molecules, causing them to lose electrons and form ions. In this process, the gaseous imidazole molecules are ionized into imidazole ions. In this way, the imidazole molecules are converted into charged imidazole ions, which are then accelerated to an energy of 80 keV and heated at a speed of 1×10 17 ions / cm 2 The implantation dose and 1μA / cm 2 The beam density of 100 nm was injected into the magnesium alloy sample. This process enables the imidazole functional groups to be introduced into the lattice of the magnesium alloy, thereby changing the surface properties of the magnesium alloy and improving its corrosion resistance and biocompatibility.

[0041] In this preferred embodiment, during the preparation of the precursor gas, the sample temperature is maintained below 50° C. by a cooling system to prevent overheating damage.

[0042] It is understandable that during the preparation of the precursor gas, the temperature of the sample is controlled by a cooling system to ensure that it is below 50°C. The purpose of this measure is to prevent the sample from overheating, thereby preventing the sample from being damaged during the process of gasifying imidazole. Specifically, the function of the cooling system is to control the temperature of the sample by cooling it down after the PLGA solution is coated on the surface of the sample and before the sample is ion-implanted. This control can prevent the sample from being overheated during the heating process, causing deformation, melting or other forms of damage to the sample. In addition, controlling the sample temperature below 50°C can also help maintain the stability of the PLGA coating and avoid chemical changes or physical damage to the coating at high temperatures. This helps to ensure that the subsequent ion implantation process can proceed smoothly and ultimately achieve the expected effect of improving the performance of the magnesium alloy.

[0043] In this preferred embodiment, the specific steps of the annealing treatment are:

[0044] After the injected sample is placed in a temperature-controlled annealing furnace, the argon protection system is started, the argon flow rate is set to 100 mL / min, the annealing temperature is set to 200° C., and the time is set to 1 hour.

[0045] It is understood that the annealing treatment is a method proposed in this application for improving the performance of magnesium alloy samples after ion implantation. The purpose of annealing treatment is to release the internal stress of the sample by heating it, and at the same time, it may change the internal structure of the sample, thereby improving its performance. The specific steps are as follows: the sample is placed in a temperature-controlled annealing furnace: the magnesium alloy sample that has been ion-implanted is placed in an annealing furnace that can control the temperature; start the argon protection system: during the annealing process, in order to prevent the sample from reacting with oxygen and causing oxidation or contamination, argon is required as a protective gas. Starting the argon protection system can ensure that the sample is always in an inert gas environment during the annealing process; set the argon flow rate: set the argon flow rate to 100mL / min. The control of the argon flow rate can ensure that the inert gas concentration in the annealing furnace is appropriate, while avoiding waste caused by excessive argon. Set the annealing temperature and time: set the annealing temperature to 200℃ and the time to 1 hour. The choice of annealing temperature and time depends on the desired annealing effect and the nature of the sample. A temperature of 200℃ can effectively promote structural changes inside the sample, and an annealing time of 1 hour is sufficient to achieve this process. Through these steps, the annealing treatment can improve the performance of the magnesium alloy sample after ion implantation, increase its mechanical strength, improve corrosion resistance or increase biocompatibility.

[0046] In this preferred embodiment, the magnesium alloy sample preparation includes:

[0047] Mechanical polishing: Use 600, 800, 1200 and 1500 grit sandpaper to polish the magnesium alloy sample in sequence until the surface is smooth without obvious scratches;

[0048] Chemical cleaning: Use ethanol and deionized water to ultrasonically clean the samples for 10 minutes each time to remove surface oil and impurities; soak the samples in 5% nitric acid solution for 1 minute to remove the oxide layer, and then rinse with deionized water;

[0049] Drying: The cleaned samples were placed in an oven at 50°C for 30 minutes.

[0050] It is understood that the magnesium alloy sample preparation steps are to ensure that the sample surface is clean and smooth, and to remove any impurities or oxide layers that may affect the subsequent ion implantation process. These steps are necessary because the ion implantation process requires a clean and uniform surface so that ions can be effectively implanted into the sample. The specific steps are as follows: Mechanical polishing: Use sandpaper of different grits (600, 800, 1200 and 1500 mesh) to polish the magnesium alloy sample in sequence until the surface is smooth and there are no obvious scratches. Mechanical polishing removes the rough parts of the sample surface by friction, making the surface smoother. Chemical cleaning: First, use ethanol and deionized water to ultrasonically clean the sample for 10 minutes each to remove surface oil and impurities. Then soak the sample in 5% nitric acid solution for 1 minute to remove the oxide layer. Finally, rinse it with deionized water. Chemical cleaning removes oil, impurities and oxide layers on the sample surface by chemical methods. Drying: Place the cleaned sample in an oven at 50°C for 30 minutes. The purpose of drying is to ensure that there is no moisture remaining on the sample surface, because moisture may affect the subsequent ion implantation process. Through these steps, the magnesium alloy sample preparation can ensure that the sample surface is clean and smooth, and remove any impurities or oxide layers that may affect the subsequent ion implantation process, thereby providing an ideal surface condition for ion implantation.

[0051] Below, the preparation steps of the present application are described by means of specific examples:

[0052] 1. Materials and Equipment

[0053] Material:

[0054] Magnesium alloy sample (such as ZK60 magnesium alloy), imidazole (C3H4N2) or its derivatives as precursor, poly(lactic-co-glycolic acid) (PLGA) solution, ethanol and deionized water;

[0055] equipment:

[0056] Ion implantation system, vacuum system (pressure ≤ 10 -6 Torr), gas delivery system, sample heating equipment, ultrasonic cleaner, temperature-controlled annealing furnace, argon protection system and spin coater;

[0057] 2. Experimental Methods

[0058] 2.1 Sample preparation

[0059] Mechanical polishing: Use 600, 800, 1200 and 1500 grit sandpaper to polish the magnesium alloy sample in sequence until the surface is smooth without obvious scratches.

[0060] Chemical cleaning: Use ethanol and deionized water to ultrasonically clean the samples for 10 minutes each time to remove surface oil and impurities.

[0061] The samples were immersed in 5% nitric acid solution for 1 minute to remove the oxide layer, and then rinsed with deionized water.

[0062] Drying: The cleaned samples were placed in an oven at 50°C for 30 minutes.

[0063] 2.2 Surface pretreatment

[0064] PLGA coating: A layer of PLGA solution was evenly coated on the surface of the magnesium alloy sample using a spin coater.

[0065] Spin coating parameters: rotation speed 3000 rpm, time 30 seconds.

[0066] The coated samples were naturally dried at room temperature to form a uniform PLGA coating.

[0067] 2.3 Ion implantation equipment preparation

[0068] Install the sample: Fix the pretreated magnesium alloy sample on the sample holder of the ion implantation equipment, ensuring that the sample surface is perpendicular to the ion beam.

[0069] Vacuuming: Start the vacuum system and reduce the vacuum degree to ≤10 -6 Torr, ensuring a high vacuum environment during ion implantation.

[0070] 2.4 Precursor gas preparation

[0071] Imidazole gasification: Imidazole (C3H4N2) is heated to 150°C to gasify it.

[0072] The vaporized imidazole is delivered to the ion source region through a gas delivery system.

[0073] 2.5 Ionization

[0074] Ionization process: In the ion source area, the gaseous imidazole is ionized by electron bombardment to generate imidazole ions (C3H3N2 + ).

[0075] 2.6 Ion Acceleration

[0076] Acceleration parameters: The imidazolium ions were accelerated to 80 keV energy using the accelerator system of the ion implantation equipment.

[0077] 2.7 Ion Implantation

[0078] Implantation parameters: Ion energy: 80keV

[0079] Injection dose: 1×10 17 ions / cm 2

[0080] Beam current density: 1μA / cm 2

[0081] Injection time: Calculate the required time based on the sample area and beam density. 2 Taking the sample as an example, the injection time is about 2 hours.

[0082] Implantation depth: With the above parameters, the implantation depth is approximately 100nm.

[0083] Cooling control: During the injection process, the sample temperature is kept below 50°C by the cooling system to prevent overheating damage.

[0084] 2.8 Post-processing

[0085] Annealing treatment: Temperature control device: Place the injected sample into a temperature-controlled annealing furnace.

[0086] Argon protection: Start the argon protection system and set the argon flow rate to 100mL / min.

[0087] Temperature setting: Set the annealing temperature to 200°C and the time to 1 hour.

[0088] Cooling: After annealing, cool naturally to room temperature.

[0089] 3. Notes

[0090] Vacuum environment: The entire ion implantation process needs to be carried out in a high vacuum environment to avoid the influence of impurity gases.

[0091] Temperature control: Ensure that the sample temperature is controllable throughout the process to avoid thermal damage.

[0092] Safety protection: Ion implantation involves high-energy radiation, and operators need to take appropriate safety protection measures.

[0093] Electrochemical corrosion test analysis of biodegradability of ZK60 magnesium alloy matrix and surface modified samples

[0094] The electrochemical corrosion test was carried out using a traditional three-electrode system. On the electrochemical workstation, each sample was placed in four test solutions at 37°C to test the change of open circuit potential over time. The potentiodynamic polarization curve was obtained with a scan rate of 1mV / s and a scan range from -300mV to +500mV of the open circuit potential. The electrochemical impedance spectrum was measured with an amplitude of 5mV and a scan frequency of 100kHz-10mHz. The corrosion current density and corrosion potential were obtained using the Tafel extrapolation method, and the electrochemical impedance spectrum was analyzed using analog circuit fitting.

[0095] Immersion test to analyze the biodegradability of ZK60 matrix and surface modified samples

[0096] The sample was heated at 20 mL / cm 2 Immerse the sample in four test solutions in the same proportion. Place an inverted funnel on the sample to ensure that all hydrogen generated on the sample surface is collected. Fill the graduated burette with the test solution and install it on the funnel. The hydrogen generated by the reaction slowly enters the burette through the funnel, causing the liquid column height of the burette to drop. Record the volume of the test solution in the burette, which is the volume of hydrogen released. Use a pH meter to monitor the change of pH value over time in real time. The hydrogen evolution rate and degradation rate of the sample are calculated.

[0097] Before the immersion experiment, each sample was weighed and the data was recorded. 2 The samples were immersed in four test solutions at a ratio of 100 μg / cm2 at 37°C for a certain period of time, and then taken out of the solution in turn. They were ultrasonically cleaned with chromic acid for 10 minutes to remove the corrosion products deposited on the surface. After the ultrasonically cleaned samples were fully dried, they were weighed twice and the data was recorded. In addition, the solutions at the corresponding time points were extracted, and the metal ion concentration in the solutions was determined by ICP-OES. The degradation rate was calculated according to the weight loss formula.

[0098] Analysis of degradation product components

[0099] After the hydrogen evolution experiment, the sample was taken out of the corresponding solution, the surface was gently rinsed with distilled water, and after drying, a surface characterization experiment was carried out to analyze the degradation products attached to the surface; SEM observation of the surface and cross-sectional corrosion morphology showed that with the change of time, the cracks of the magnesium alloy with the addition of imidazolium ions were lighter than those of the magnesium alloy without the addition of imidazolium ions, and no deep pits or unevenness appeared after 31 days.

[0100] The anodic region of the polarization curve is related to the dissolution of the alloy, while the cathodic region involves the hydrogen evolution reaction. The electrochemical parameters (Ecorr and Icorr) determined by the Tafe l extrapolation method are listed in Table 1. Moreover, the corrosion current density is an important parameter for evaluating the corrosion performance of the sample. The smaller the corrosion current density, the stronger the corrosion resistance of the sample. The Icorr value of ZK60 magnesium alloy in Hank's solution is (293.84±8.45)μA / cm 2 , with the injection of imidazolium ions, the I corr value decreased by 6 times. In DMEM solution, the I corr values ​​of the injected samples were all lower than those of ZK60 magnesium alloy, indicating that hydroxyl and carboxyl groups can significantly improve the corrosion resistance of ZK60 magnesium alloy. This is because hydroxyl / carboxyl ions form a compound-rich functional layer on the surface of ZK60 magnesium alloy, which provides a barrier for the corrosion of ZK60 magnesium alloy. After the injection of imidazolium ions, the metal oxides and hydroxides in the modified layer, as well as the corrosion products generated in the early stage of corrosion, become the initial barrier to block the erosion of the solution and resist the penetration of solution ions. As the corrosion intensifies, the insoluble carbonate can further hinder the ion erosion of the substrate. In addition, for DMEM solution, the imidazolium ion groups in the modified layer are beneficial to the adsorption of amino acid ions in DMEM to a certain extent, and the amino acid ions adsorbed on the surface enhance the corrosion resistance of the sample. Therefore, compared with the ZK60 sample without injection, the composite layer formed on the surface of the ZK60 magnesium alloy injected with imidazolium ions is more stable during the corrosion process due to the presence of groups, and has a stronger protective effect on the matrix, which significantly reduces the corrosion rate of the imidazolium ion-implanted sample in both solutions.

[0101] Table 1

[0102]

[0103] Moreover, after ion implantation into magnesium alloy, the hardness and elastic modulus of the sample after ion implantation are greater than those of the matrix magnesium alloy, and tend to be stable when the indentation depth is deeper (the sample is measured by a nanoindentation instrument, and the results are shown in Figure 1 ). This is mainly due to the compressive strain caused by the ion implantation process. The stress generated causes the lattice structure to deform and hard compounds to form on the surface, which leads to a certain improvement in the mechanical properties of magnesium alloys.

[0104] In summary, the present invention can effectively improve the corrosion resistance and biocompatibility of magnesium alloy by coating a layer of PLGA coating on the surface of magnesium alloy, thereby expanding its application range in the biomedical field. By using a spin coater for surface pretreatment, it can be ensured that the PLGA coating is evenly coated on the surface of magnesium alloy, further improving the stability and reliability of the coating. During the ion implantation process, by controlling the vacuum degree at ≤10 -6Torr, which can avoid the influence of impurity gas on the injection process and ensure the purity and effect of ion injection. Heating imidazole to 150℃ for gasification is beneficial to improve the gasification efficiency of imidazole, thereby ensuring the imidazole ion concentration in the ion source area and further improving the effect of ion injection. Using electron bombardment to ionize gaseous imidazole can effectively convert imidazole molecules into imidazole ions, which is beneficial to the subsequent ion injection process. When preparing the precursor gas, the sample temperature is kept below 50℃ by the cooling system to prevent the sample from being damaged by overheating, ensuring the safety and stability of the sample. During the annealing process, the structural stability and performance of the magnesium alloy sample after injection can be effectively improved by starting the argon protection system and controlling the annealing temperature. Mechanical polishing and chemical cleaning of magnesium alloy samples can remove impurities and oxide layers on the sample surface, providing a good foundation for subsequent surface pretreatment and ion injection.

[0105] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A method for implanting organic functional group ions into a magnesium alloy, characterized in that: include: Sample preparation; Surface pretreatment: coating the sample with PLGA solution and drying it naturally to form a PLGA coating; The sample is fixed on the ion implantation device and then vacuumed; The precursor gas was prepared by vaporizing imidazole and delivering it to the ion source area; ionizing imidazole to generate imidazole ions; accelerating imidazole ions to 80 keV energy; and ionizing imidazole ions to generate imidazole ions at 1×10 17 ions / cm 2 Implantation dose and 1μA / cm 2 Ions were implanted at a beam density of 100 nm and an implantation depth of 100 nm. After annealing, the process is followed by natural cooling to room temperature.

2. The method for implanting organic functional group ions into magnesium alloy according to claim 1, characterized in that: The surface pretreatment is performed by using a spin coater, and the coating parameters are a rotation speed of 3000 rpm and a time of 30 seconds.

3. The method for implanting organic functional group ions into magnesium alloy according to claim 1, characterized in that: The vacuum degree of the vacuum pumping is ≤10 -6 Torr.

4. The method for implanting organic functional group ions into magnesium alloy according to claim 1, characterized in that: The operation of gasifying imidazole in the precursor gas preparation is: heating the imidazole to 150° C. to gasify it.

5. The method for implanting organic functional group ions into magnesium alloy according to claim 1, characterized in that: The ionized imidazole is specifically: in the ion source region, the gaseous imidazole is ionized by electron bombardment to generate imidazole ions.

6. The method for implanting organic functional group ions into magnesium alloy according to claim 1, characterized in that: During the preparation of the precursor gas, the sample temperature is maintained below 50° C. by a cooling system to prevent overheating and damage.

7. The method for implanting organic functional group ions into magnesium alloy according to claim 1, characterized in that: The specific steps of the annealing treatment are: After the injected sample is placed in a temperature-controlled annealing furnace, the argon protection system is started, the argon flow rate is set to 100 mL / min, the annealing temperature is set to 200° C., and the time is set to 1 hour.

8. The method for implanting organic functional group ions into magnesium alloy according to claim 1, characterized in that: The magnesium alloy sample preparation includes: Mechanical polishing: Use 600, 800, 1200 and 1500 grit sandpaper to polish the magnesium alloy sample in sequence until the surface is smooth without obvious scratches; Chemical cleaning: Use ethanol and deionized water to ultrasonically clean the samples for 10 minutes each time to remove surface oil and impurities; soak the samples in 5% nitric acid solution for 1 minute to remove the oxide layer, and then rinse with deionized water; Drying: The cleaned samples were placed in an oven at 50°C for 30 minutes.

Citation Information

Cited By

  • Surface modification method for implanting magnesium ions into polylactic acid implant and application of surface modification method

    CN121534225A